(untitled) (Materiali di Estetica. Terza serie, 2021)
The article aims to demonstrate the influence of Antonio Banfi and Corrente in the Milanese architectural culture of the 1930s. Banfi’s teaching offered architects an opportunity to rethink the project in philosophical terms of reaction to the «crisis of culture and civilization» of the time, emphasizing the urgency of a more direct and intimately involved dialogue on the part of architects towards their models. The problem of the relationship between form and technique, nature and construction, freedom of design and moral sense then became central after the war.